Computer Aided Design of Tractor operated Pea Pod Picker. Issue 1 (August 2021) - Bhad, R; Goyal, R; Singh, M; Jain, L; Singh, S
Abstract: India isn't just the biggest consumer of green peas, yet in addition it takes second place in worldwide green pea cultivation, following China. The area under peas in India was 540.5 thousand hectares in 2017-18. Presently, green pea crop is cultivated on approximate thirty-five thousand hectares in Punjab. Out of this 90% area is cultivated under early maturing variety of green pea. Picking of green pea is labor intensive. Therefore, to lower the involvement of manual labor, mechanized picking of pod is required. A conceptual design of tractor operated pea pod picker was done by keeping in view the harvesting of AP-3 pea variety and agronomic practices. Based upon review, important operational and design parameters were selected for the study. A computer aided design of pea pod picker was done. All the sub-assemblies like crop guide, picking drum, belt conveyor and aspirator were created using Creo 3.0 software (Make: PTC Creo) at PAU, Ludhiana. Based upon 2D drawings, a tractor operated pea pod picker was developed and fabricated.